2004
DOI: 10.1002/pssc.200304864
|View full text |Cite
|
Sign up to set email alerts
|

Silicon excess and thermal annealing effects on the photoluminescence of SiO2 and silicon rich oxide super enriched with siliscon implantation

Abstract: The off-stoichiometry silicon oxide SiO x (x < 2), known as silicon-rich oxide (SRO), and siliconimplanted thermal silicon oxide (SITO) have shown noticeable photoluminescence (PL) at room temperature. Recently, many efforts to increase the PL in these materials have been made. In our experiments, a considerable increase of the visible emission has been observed when the SRO is super-enriched by silicon implantation. In this experiment, SITO and LPCVD-SRO with different silicon excess, Si implanted and no impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Wavelength spectrum from 650 to 800 nm is observed for SRO 10,20,30 . This emission range is characteristic of SRO annealed films on silicon [7]. It is known that thermal annealing, size of Si nanocrystals, and the density of states within the SRO film play a fundamental role in the PL spectra.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Wavelength spectrum from 650 to 800 nm is observed for SRO 10,20,30 . This emission range is characteristic of SRO annealed films on silicon [7]. It is known that thermal annealing, size of Si nanocrystals, and the density of states within the SRO film play a fundamental role in the PL spectra.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, we can assume that the absorption and emission processes in SRO films are connected with electrons decay [7] between donor-acceptor pairs localized inside the silicon oxide band gap. Traps inside the band gap can accept or donate one electron turning into donor-acceptor pairs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these applications, compatibility of such materials and the conventional IC's silicon processes is desirable. It has been demonstrated that Silicon Rich Oxide (SRO) films subjected to high-temperature annealing exhibit efficient photoluminescence (PL) [7,8]. Besides, their chemical stability and robustness promise high suitability for integrated electronic and optic device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among other properties, Si-nCs exhibit photoluminescence in the visible range, attributed to quantum confinement effects and to defects at the interfaces [1]. Additionally, some studies have been performed to use the nCs as charge storing centers in single buried layers [2,3] or superlattices of polysilicon [4].…”
Section: Introductionmentioning
confidence: 99%